Broke, Ill, and Obese: The Effect of Household Debt on Health - Matthias Keese; Hendrik Schmitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We analyze the effect of household indebtedness on different health outcomes using data from the German Socio-Economic Panel from 1999-2009. To establish a causal effect, we rely on (a) fixed-effects methods, (b) a subsample of constantly employed individuals, and (c) lagged debt variables to rule out problems of reverse causality. We apply different measures of household indebtedness, such as the percentage shares of household income spent on consumer credit and home loan repayments (which indicate the severity of household indebtedness) and a binary variable of relative overindebtedness (which indicates a precarious debt situation). We find all debt measures to be strongly correlated with health satisfaction, mental health, and obesity. Controlling for unobserved heterogeneity and reversed causality we find evidence that household debt also causally deteriorates physical and mental health. However, there is no causal effect on being obese.
Keywords: D12; D14; I12; 330; Debt; health satisfaction; mental health; obesity; fixed-effects; Private Verschuldung; Gesundheit; Schätzung; Deutschland